AN ANALYTICAL ASSESSMENT OF POULTRY INDUSTRY AND ADOPTION OF POTENTIAL VALUE ADDITION INTERVENTIONS IN BY-PRODUCT PROCESSING TO ENHANCE PROFITABILITY – IBADAN, OYO STATE, NIGERIA - Taofeek Ayodeji Ayo-Bello; Osaige John Afodu; Tolulope Ogunleye; Lois Ndubuisi-Ogbonna; Jesubukunmi Omoniyi (Socio-Economics/Agribusiness Department, 2021)
The need to diversify the Nigerian economy calls for value chain development of the agricultural and livestock sector. The main purpose of the study is to seek additional source of income for poultry producers through the processing of selected poultry by-products in the study area. A baseline study of poultry enterprises was carried out in Ibadan, Oyo State, Nigeria using a purposive sampling technique. A structured questionnaire was used in the collection of data and data collected was analyzed using descriptive statistics, gross margin analysis and Logit regression. The result showed and exhibited a gross margin ratio of 82.9% indicating profitability of enterprise. The regression result revealed that the adoption of poultry by-products processing was by different factors at different level of significance in organic fertilizer was influence. The study revealed that the respondents ranked high cost of machineries (25%) as the major problem encountered by them. It was recommended that awareness should be intensified on management poultry by-products; encouragement of Public-Private Partnership (PPP), towards the provision of adequate infrastructure need for commercialization of poultry by-products processing in Nigeria.